Evaluation of nine formulas for estimating the body surface area of children with hematological malignancies - Qing Wu; Yan Zhou; Xin Fan; Huan Ma; Wenrui Gu; Fengjun Sun (Frontiers Media S.A., 2022)
ObjectivesBody surface area (BSA) is an important parameter in clinical practice for children. To find out the most accurate BSA formula for Chinese children, nine formulas were compared.MethodsThis single-center study comprised children who were diagnosed with acute lymphoblastic leukemia and treated with anticancer agents in a specialized children's hospital in China from January 2017 to December 2020. The BSA values were calculated using the formulas from Boyd, Banerjee and Bhattacharya, Costeff, Fujimoto and Watanabe, Haycock, Gehan and George, Mosteller, Stevenson and a Pediatrics textbook. The arithmetic mean of formulas was calculated as the "gold standard" for comparison.ResultsA total of 666 children (389 males and 277 females) were included. All nine formulas showed a strong positive correlation with the "gold standard." Underestimation was observed with the Banerjee and Bhattacharya, Fujimoto and Watanabe formulas. The Gehan and George formula showed overestimation. Values estimated from the Haycock and Mosteller formulas were the closest to the mean BSA.ConclusionThe Haycock and Mosteller formulas are the most recommended formulas for Chinese children with hematological malignancies.